Synthesis and Antitumor Activities of Derivatives of the Marine Mangrove Fungal Metabolite Deoxybostrycin - Zhi-Gang She; Yuhua Long; Yong-Cheng Lin; Sheng-Ping Chen; Jue-Heng Wu; Bing Yang; Jia Li; Li-Li Zhong; Hong Chen; Xun Zhu (Marine Drugs, 2012)
Deoxybostrycin (1) is an anthraquinone compound derived from the marine mangrove fungus Nigrospora sp. No. 1403 and has potential to be a lead for new drugs because of its various biological properties. A series of new derivatives (2–22) of deoxybostrycin were synthesized. The in vitro cytotoxicity of all the new compounds was tested against MDA-MB-435, HepG2 and HCT-116 cancer cell lines. Most of the compounds exhibit strong cytotoxicity with IC50 values ranging from 0.62 to 10 μM. Compounds 19, 21 display comparable cytotoxicity against MDA-MB-435 to epirubicin, the positive control. The primary screening results indicate that the deoxybostrycin derivatives might be a valuable source of new potent anticancer drug candidates.